The consumer psychological contract: conceptual foundations and construct definition (2017)
A psychological contract is an unwritten characterization of a relationship. This concept has been defined and used to evaluate the relationship between employees and their organization. The purpose of this paper is to define the psychological contract construct in a marketing context understanding the relationship consumers’ hold with an organization. This paper reviews the development of the psychological contract construct: the idea was born within the social exchange theory; it was later defined, operationalized, and applied in the organizational behavior literature. The consumer behavior literature has rarely included the psychological contract construct. Thus, this paper explains the consumer psychological contract considering its dimensions: transactional and relational. Finally, the paper provides insights for its application to the consumer behavior arena.